Hyponatremia in lower respiratory tract infections - K. M., Chaitra; Kumar N., Mohan; Reddy G., Saipraneeth (International Journal of Contemporary Pediatrics, 2016)
Background: Hyponatremia is the most common electrolyte abnormality seen in PICU. The main Objective is to characterize the relationship between hyponatremia within 2 hours of admission to the intensive care unit, in the setting of lower respiratory tract infections, and to investigate whether there is a link between hyponatremia and the severity and outcome of LRTI. Methods: This was a prospective medical chart review of all children admitted to the PICU with a diagnosis of lower respiratory tract infections such as pneumonia, bronchiolitis, wheezing, empyema. Between Jan 1, 2015, and june 30, 2015. Severity of Hyponatremia was defined as mild= serum sodium concentration 131-135 mmol/L, moderate = 126-130 mmol/L, and severe HNa = less than 125 mmol/L (the normal values for serum sodium at our institution are 135-145 mmol/L). Results: The present study showed that hyponatremia was a frequent finding in children with bronchopneumonia 28 (46.7%). Lobar pneumonia which was next common respiratory infection in our study had hyponatremia in 6 cases (50%) In our study it was found that all cases with empyema had hyponatremia (100%). Bronchiolitis and wheeze associated LRTI relatively had less incidence of hyponatremia in our study. on the whole, it was found that among all hyponatremia cases in lower respiratory tract infection, mild hyponatremia was common (70.7%), followed by moderate and only 3 cases were having severe hyponatremia. Conclusions: Our study suggests that all cases of empyema develop hyponatremia is a new association derived. Patients with lobar segmental pneumonia and bronchopneumonia are at higher risk of developing moderate or severe Hyponatremia. Thus the appropriate fluid therapy must be carefully arranged in children with lower respiratory tract infection.